Synergistic effect of Azotobacter sp. and bulking agents on hydrocarbon bioremediation performance in petroleum-contaminated soil - Suryatmana, Pujawati; Hindersah, Reginawanti; Setiawati, Mieke Rochimi; Parnadi, Wahyudi Widyatmoko; Zulkifliani, Zulkifliani; Syafrizal, Syafrizal (Brawijaya University, 2026)
Petroleum hydrocarbon contamination is a critical environmental issue in tropical soils. This study evaluated the effects of Azotobacter sp. and two bulking agents: rice husk biochar (RHB) and spent oyster mushroom substrate (SOMS), on a microcosm scale of petroleum-contaminated Ultisols. The experiment design used a randomized block design (RBD). Treatments included single and combined applications of Azotobacter sp. and bulking agents. Results showed that SOMS amendment yielded significantly (p< 0.05) the highest microbial populations, fungi (43.23 × 104 CFU g?¹) and bacteria (42.633 x 106 CFU g?¹), the highest degradation rate (0.040 mg L?¹ cell?¹ day?¹) and efficiency (81.62%) compared with the control (0.012 mg L?¹ cell?¹ day?¹; 39.55%). Azotobacter sp. inoculation combined with SOMS increased Azotobacter sp. density (59.167 × 104 CFU g?¹). Azotobacter sp. produced a biosurfactant that was dominated by Oleic acid. The hydrocarbon biodegradation rate improvements were linked to increased soil pH, nutrient availability, and biosurfactant production by Azotobacter sp. Meanwhile, RHB alone showed lower performance, but when combined with Azotobacter sp. improved degradation relative to the control. Integrating Azotobacter sp. inoculation with nutrient-rich bulking agents, particularly SOMS, significantly improves petroleum hydrocarbon biodegradation in Ultisols by optimizing physicochemical and biological conditions for indigenous microbial consortia.